Accuracy and Reliability of Digital Dental Models Obtained by Intraoral Scans Compared with Plaster Models - Vo Huyen Bao Tran; Tran Hung Lam; Truong Nhut Khue; Tran Ngoc Quang Phi; Hoang Viet (Applied Sciences)
Introduction: In orthodontics, determining the parameters of tooth size and dental arch and conducting Bolton analysis is crucial for diagnosis, treatment planning, and patient outcomes. This study evaluates the accuracy and reliability of measuring dental-arch dimensions on digital models created using the CEREC Primescan intraoral scanner, compared to measurements taken from plaster models. Methods: The study included two types of dental models (plaster and intraoral scan) from sixty-three subjects. Impressions were taken to create plaster models, and the subjects’ mouths were scanned with the CEREC Primescan system (Dentsply Sirona, Charlotte, NC) to create digital models. Intra-arch measurements included tooth heights and widths, overjet, and overbite. The arch width and depth were examined at the first permanent upper or lower molar. The paired t-test and Bland–Altman plot were used to determine the accuracy, while intra-rater and inter-rater correlation coefficient values were calculated to assess the reliability of measurements from the intraoral scan compared to those from the plaster model. Results: For tooth heights, there was a statistically significant difference in only one measurement (tooth 34) between the plaster and digital models, with an average difference of 0.01 mm. For tooth widths, there was a statistically significant difference in only one measurement (tooth 15) with an average difference of 0.03 mm. The Bland–Altman plots of almost all of measurements of tooth heights and widths showed that differences between the two models were within the limits of agreement. The inter- and intra-rater correlation coefficient values for measurements on the digital model were found to be statistically insignificant. Conclusion: Measuring dental dimensions on digital models obtained through the Primescan intraoral digital system yielded similar results to those obtained from plaster models and showed excellent reliability, indicating its potential application in clinical practice.